The American college town - Gumprecht, Blake (University of Massachusetts Press, 2008)
"In this book - the first work published on the subject - Blake Gumprecht identifies the distinguishing features of college towns, explains why they have developed as they have in the United States, and examines in depth various characteristics that make them unusual. In eight thematic chapters, he explores some of the most interesting aspects of college towns - their distinctive residential and commercial districts, their unconventional political cultures, their status as bohemian islands, their emergence as high-tech centers, and more. Each of these chapters focuses on a single college town as an example, while providing additional evidence from other towns." "Lively, richly detailed, and profusely illustrated with original maps and photographs as well as historical images, this is an important book that firmly establishes the college town as an integral component of the American experience."--Jacket.